Nurses’ compliance in intravenous injection among patients with extreme nutritional status: Implications for patient safety - Idayanti Idayanti; Kristiyani Herda Rophi (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Intravenous (IV) injection safety is a critical aspect of nursing practice, particularly for patients with extreme nutritional status. Nutritional imbalance can affect vascular integrity and tissue resistance, potentially reducing adherence to standard procedures. This study aimed to examine the relationship between nurses’ compliance with intravenous injection procedures and patient safety among individuals with extreme nutritional conditions in a hospital setting. This cross-sectional observational study was conducted at Arifin Achmad General Hospital, Pekanbaru, between January and March 2024, and involved 60 adult patients with undernutrition (BMI < 18.5 kg/m²) or obesity (BMI ≥ 30 kg/m²). Compliance was measured using a checklist based on the WHO and Ministry of Health guidelines, and patient safety was assessed through IV-related complications. Data were analyzed using chi-square and multivariate logistic regression analyses. The results showed a compliance rate of 72.5% and a significant relationship between compliance and the incidence of complications (p = 0.008). Noncompliance increased the risk of complications by 2.8 times (OR = 2.8; p = 0.014). In conclusion, nurses’ adherence to IV injection procedures significantly affects patient safety. Continuous training and adaptive protocols that consider patients’ nutritional status are recommended to enhance nursing service quality.